Efficient production of citric acid in segmented fermentation using Aspergillus niger based on recycling of a pellet-dispersion strategy. Issue 107 (3rd November 2016) - Wang, Baoshi; Chen, Jian; Li, Hua; Sun, Fuxin; Li, Youran; Shi, Guiyang
Abstract : Segmentation recycling fermentation based on a pellet-dispersion strategy to reconstruct the traditional citric acid batch fermentation process is reported. Abstract : Citric acid (CA), as the most important platform compound, has attracted much attention because of its broad applications in many areas. Here, we constructed a segmentation fermentation process which effectively separated cell growth and CA production. Through a pellet-dispersion strategy, the CA yield decline caused by the mycelium structure of Aspergillus niger was solved. In particular, CA production was significantly increased from 70.3 g L −1 to 97.0 g L −1 . Furthermore, the segmentation fermentation conditions were optimized to improve the CA production. Evidence showed that the process was stable during ten batches of recycling fermentation in 5 L five-conjoined-fermenters, from which the CA yield even increased by 1.4 g L −1 (by 1.26%) compared with the control. All of these results confirm that the strategy could enhance productivity and avoid the traditional long process (about 30 days) of seed culturing (including spore preparation). It could be also applied in other fermentation industries involving filamentous fungi.